2022
DOI: 10.1007/s11356-021-18445-8
|View full text |Cite
|
Sign up to set email alerts
|

Sources of airborne particulate matter-bound metals and spatial-seasonal variability of health risk potentials in four large cities, South Korea

Abstract: Fifteen airborne particulate matter-bound metals were analyzed at 14 sites in four large cities (Seoul, Incheon, Busan, Daegu) in South Korea, between August 2013 and June 2017. Among the seven sources resolved by positive matrix factorization, soil dust and marine aerosol accounted for the largest and second largest portions in the three cities; however, in Seoul, soil dust and traffic occupied the largest and the second largest, respectively. Non-carcinogenic risk assessed by inhalation of eight metals (Cd, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…The highest total CR of 7.7 × 10 −5 for adults (about 77 cancer cases per 1000000 adults) occurs in Dhaka followed by Kanpur and Hanoi. The CR caused only by As in Dhaka, Kanpur, and Hanoi exceeds the benchmark 38,39 of 1 × 10 −5 and is higher than the sum of CR caused by the remaining elements, suggesting a concerning level of atmospheric As at these sites. Estimates based on global simulation from Zhang et al 40 indicate similarly high CR caused by atmospheric As in several regions, including Asian countries such as India and Bangladesh.…”
Section: Health Risk Assessmentmentioning
confidence: 82%
“…The highest total CR of 7.7 × 10 −5 for adults (about 77 cancer cases per 1000000 adults) occurs in Dhaka followed by Kanpur and Hanoi. The CR caused only by As in Dhaka, Kanpur, and Hanoi exceeds the benchmark 38,39 of 1 × 10 −5 and is higher than the sum of CR caused by the remaining elements, suggesting a concerning level of atmospheric As at these sites. Estimates based on global simulation from Zhang et al 40 indicate similarly high CR caused by atmospheric As in several regions, including Asian countries such as India and Bangladesh.…”
Section: Health Risk Assessmentmentioning
confidence: 82%
“…Generally, heavy metals are amalgamated with PM [ 8 ] and mainly originate from diesel and gasoline exhaust fumes from local traffic and industrial areas [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have shown that exposure to NO 2 , SO 2 , and PM2.5 is a risk factor for stillbirth and spontaneous abortion, supporting the notion that exposure to NO 2 , SO 2 , and PM2.5 can affect the fetus [ 20 , 21 ]. Regarding neurodevelopment, it is known that PM2.5 can induce oxidative stress and an inflammatory response [ 8 ] and that both oxidative stress and an inflammatory response can affect the expression of brain-derived neurotrophic factor (BDNF) and cyclic AMP response element-binding protein (CREB), which are well-known neurodevelopment factors [ 22 , 23 , 24 ]. Some studies have demonstrated that exposure to PM2.5 is related to changes in the expression of BDNF and CREB [ 25 , 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…Understanding the health risks associated with the metal elements of PM 2.5 and clarifying their respective sources are crucial for developing cost-effective risk mitigation strategies to protect public health. The health effects of emission sources can be analyzed by linking source profiles obtained through receptor modeling to risk assessment model [15,16].…”
Section: Introductionmentioning
confidence: 99%